The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.5551/jat.12.111
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Serum Ubiquinol-10 and Ubiquinone-10 Levels by Atorvastatin in Hypercholesterolemic Patients

Abstract: Reduction of serum cholesterol levels with statin therapy decreases the risk of coronary heart disease. Inhibition of HMG-CoA reductase by statin results in decreased synthesis of cholesterol and other products downstream of mevalonate, which may produce adverse effects in statin therapy. We studied the reductions of serum ubiquinol-10 and ubiquinone-10 levels in hypercholesterolemic patients treated with atorvastatin. Fourteen patients were treated with 10 mg/day of atorvastatin, and serum lipid, ubiquinol-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 33 publications
5
54
0
9
Order By: Relevance
“…Suppressed biosynthesis of ubiquinone (CoQ10), an essential factor in the electron-transfer system in mitochondria, may result in delayed ATP production in pancreatic cells and thereby impair insulin release. It was recently shown that atorvastatin treatment resulted in a reduction of serum CoQ10 levels, which was positively correlated with LDL cholesterol levels 35) . These mechanisms may differ by the property of statins.…”
Section: Mechanisms Of the Effects Of Statins On Glucose Metabolismmentioning
confidence: 96%
“…Suppressed biosynthesis of ubiquinone (CoQ10), an essential factor in the electron-transfer system in mitochondria, may result in delayed ATP production in pancreatic cells and thereby impair insulin release. It was recently shown that atorvastatin treatment resulted in a reduction of serum CoQ10 levels, which was positively correlated with LDL cholesterol levels 35) . These mechanisms may differ by the property of statins.…”
Section: Mechanisms Of the Effects Of Statins On Glucose Metabolismmentioning
confidence: 96%
“…Even low-normal free thyroxin levels in patients with euthyroidism have been associated with insulin resistance (22,23). Thyroid disease induces mitochondrial dysfunction (24)(25)(26)(27), and statins reduce levels of coenzyme Q10, a component of the electron transport chain involved in the process of ATP generation (28), also leading to mitochondrial dysfunction as well as causing reduced insulin release and pancreatic b-cell failure and contributing to the development of DM (29)(30)(31)(32). Downregulation of GLUT4 in adipocytes has also been shown to be a result of statin treatment, an effect that has been explained in terms of reduced isoprenoid biosynthesis (33).…”
Section: Discussionmentioning
confidence: 99%
“…16, The antioxidant effect of coenzyme Q10 is greater than vitamin E. 17 Coenzyme Q10 is also known to enhance the availability of other antioxidants such as vitamin C, vitamin E and betacarotene. 18 Also, coenzyme Q10 inhibits low-density lipoproteins (LDL) oxidation in vitro and lipid peroxidation in vivo and scavenges free radicals.…”
Section: Introductionmentioning
confidence: 99%